2016
DOI: 10.18632/oncotarget.13334
|View full text |Cite
|
Sign up to set email alerts
|

Unique epigenetic gene profiles define human breast cancers with poor prognosis

Abstract: Epigenetic enzymes are at the nexus of cellular regulatory cascades and can drive cancer-specific deregulation at all stages of the oncogenic process, yet little is known about their prognostic value in human patients. Here, we used qRT-PCR to profile at high resolution the expression of fifty-five epigenetic genes in over one hundred human breast cancer samples and patient-matched benign tissues. We correlated expression patterns with clinical and histological parameters and validated our findings in two inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Bioinformatics analysis based on TCGA was conducted to reveal SUV39H2 and other novel genes (SUV39H1, DNMT3B, EZH2 and AURKB) expressions significantly increase in triple negative (TN) disease and positively associate with high Ki67 levels, TN status and tumor grade. The higher expression of SUV39H2 correlated with shorter survival time [61]. SUV39H2 appears to be associated with more aggressive phenotypes and metastatic biology.…”
Section: Suv39h2 In Breast Cancermentioning
confidence: 86%
“…Bioinformatics analysis based on TCGA was conducted to reveal SUV39H2 and other novel genes (SUV39H1, DNMT3B, EZH2 and AURKB) expressions significantly increase in triple negative (TN) disease and positively associate with high Ki67 levels, TN status and tumor grade. The higher expression of SUV39H2 correlated with shorter survival time [61]. SUV39H2 appears to be associated with more aggressive phenotypes and metastatic biology.…”
Section: Suv39h2 In Breast Cancermentioning
confidence: 86%
“…Several factors can contribute to transcriptomic variations in breast cancer subtypes, such as differences in the abundance of wild type or mutated transcription factors, mutations that impact the stability and turnover of RNA transcripts, and dysregulation of histone-modifying enzymes [ 13 ]. It is important to determine the relationship between phenotypic subclasses and transcription profiles [ 16 , 64 , 94 ] to elucidate cancer mechanisms and drug targets for more effective treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Several landmark studies have revealed that hyperactivity of the histone-methyltransferase enhancer of zeste 1 and 2 (EZH1, EZH2), which generates the histone PTM H3K27me3, is a feature shared by many types of cancer (recently reviewed in [ 7 ]). In breast cancer, elevated EZH2 has been linked to cell proliferation and metastasis [ 8 , 9 ] and a poor prognosis for breast cancer patients [ 10 13 ]. In stem cells and cancer cells, EZH2 generates H3K27me3 marks at nucleosomes (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors can contribute to transcriptomic variations in breast cancer subtypes, such as differences in the abundance of wild type or mutated transcription factors, mutations that impact the stability and turnover of RNA transcripts, and dysregulation of histone-modifying enzymes [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Several landmark studies have revealed that hyperactivity of the histone-methyltransferase enhancer of zeste 1 and 2 (EZH1, EZH2), which generates the histone PTM H3K27me3, is a feature shared by many types of cancer (recently reviewed in [7] ). In breast cancer, elevated EZH2 has been linked to cell proliferation and metastasis [8,9] and a poor prognosis for breast cancer patients [10][11][12][13] . In stem cells and cancer cells, EZH2 generates H3K27me3 mark at nucleosomes ( Fig.…”
Section: Introductionmentioning
confidence: 99%